Turbine optimization potential to improve automotive Rankine cycle performance. (5th March 2021) - Alshammari, Fuhaid; Pesyridis, Apostolos; Elashmawy, Mohamed
Highlights: Radial turbines are suitable candidates for unstable heat source conditions. Engine power and BSFC are substantially improved after installing the ORC system. The 1D model has proven effective obtaining good agreement with the 3D CFD results. 3D CFD optimization improved turbine flow aerodynamics and powertrain performance. Optimized turbine isentropic efficiency increased by 10.68% at nominal conditions. Abstract: Waste heat recovery (WHR) systems based on organic Rankine cycle (ORC) are gaining increasing interests for reducing the exhaust emissions and fuel consumption of heavy-duty diesel engines. The expansion machine (i.e. radial inflow turbine) is a critical component of the ORC system and its performance substantially influences the overall powertrain performance. Therefore, this study presents an effective methodology that combines the previously developed mean-line design model, a 3D CFD analysis and a multi-objective optimization technique for a high pressure-ratio radial turbine. The exhaust gases of a 7.25ℓ heavy-duty diesel engine is used as the heat source with NOVEC 649 as the cycle working fluid. The optimized radial turbine is then integrated with the powertrain system to explore its effects on engine power, BSFC and cycle efficiency, at both design and off-design conditions. The ORC improved engine power and BSFC by maximum values of 5.7% and 5.4%, respectively, with the baseline turbine. With the optimized turbine, the power and BSFC improvements reached 6.15 and 5.8%, respectively. Compared to the baseline turbine, the optimized turbine isentropic efficiency increased by 10.68% at nominal conditions. As a result, the cycle thermal efficiency was significantly improved presenting 8.2% higher efficiency compared to the cycle with baseline turbine. The combination methodology has proven effective as it significantly improved the powertrain performance.